CONCEPTUAL APPROACHES TO STATE REGULATION OF SUSTAINABLE DEVELOPMENT IN UKRAINE - Buryk Z.M. (Pressing Problems of Public Administration, 2017)
Theoretical and conceptual approaches of state regulation of sustainable development should bebased on the development of economic, environmental and social spheres. Systematized strategicposition to introduce the conceptual bases of state regulation of sustainable development, whichregulate and govern the transition to sustainable development in Ukraine from the Independenceperiod and outlined the problems of their implementation. The selected lines and are key principles(conditions) effective implementation of the Strategy for Sustainable Development “Ukraine – 2020”.